A contribuição da atividade cineclubística do Chaplin Club (1928-1931) para a maturidade da crítica cinematográfica brasileira - Lourenço, Júlio César (2011)
This survey aimed to study Chaplin Club's route, the first Brazilian regular cineclub that between 1928 to 1931, when it made itself recognized as a legitimate place of cinema and discussion, established a new way to think of cinema as art and not only about entertainment. The debates and the theoretical works of this pioneer cineclub inaugurated the cinematographic national critique. Investigating Chaplin Club's social and intellectual history includes to understand how the cinema culture was absorbed and construed in Brazil. I render problematic that cineclub as an intellectual forum presenting it as a social practice aiming to understand it's production, it's rituals, it's symbolisms and it's meaning. That way, I studied it's association considering it's existence period, it's main directors, the exhibited movies, it's main debated themes, the influences it caused and the treatment it gave to Brazilian cinema. I also investigated which were the proposals to this club's constitution, analyzing since it's premises to it's limitations and contradictions, the society images which functioned the ways of a social and intellectual identity that it's components were inclined to assume. Eventually, which were Chaplin Club's social and cultural goals. The interest was to understand the concrete experience of life, exposing cultural practices of a determined society; the formalization of this practice in symbolical products and the social structures that influenced this product.